ZIF-8-based oxygen reduction reaction catalyst prepared from one-pot and stepwise ion- and liquid-assisted grinding modified with tris-1, 10-phenanthroline iron (II) perchlorate. (19th January 2022) - Yang, Wonseok; Cha, Dowon; Lee, Wooyeol; Kim, Yongchan
Abstract: In this study, a one-pot ion- and liquid-assisted grinding (ILAG) synthesis of ZIF-8-based catalysts was proposed and compared with a conventional stepwise synthesis to determine an appropriate method for proton exchange membrane fuel cells (PEMFCs). The performance characteristics of one-pot- and stepwise-synthesis catalysts were measured by various physicochemical and electrochemical characterization methods. In lab-scale production, the material cost of the one-pot-synthesis catalyst was seven times lower than that of the stepwise-synthesis catalyst. The surface structural characteristics of the one-pot- and stepwise-synthesis catalysts were identical, and the two catalysts showed similar onset potentials that were close to that of a Pt/C. However, based on PEMFC tests, the maximum power density of the one-pot-synthesis catalyst was lower than that of the stepwise-synthesis catalyst owing to the smaller micropore area of one-pot-synthesis catalyst. Nonetheless, the difference between maximum power densities was only 9.6% despite the large disparity in the material cost. Thus, the proposed one-pot-synthesis catalyst can be recommended as a promising non-platinum group metal (PGM) catalyst, but further research to improve its micropore area and performance is required. Highlights: A novel one-pot synthesis of ZIF-8-based non-PGM catalysts is proposed and tested. The characteristics of one-pot and stepwise synthesis catalysts are compared. In lab-scale production, the material cost of the one-pot catalyst is 7 times lower. The ORR onset potentials of the two catalysts are identical and close to Pt catalyst. In PEMFC tests, the maximum power density of the one-pot catalyst is lower by 9.6%.